Investigating the Effectiveness of Positive-thinking-based Poetry Therapy on Infertility Stress and Psychological Well-being in Infertile Women - Fatemeh Sepahvand; Fatemeh Rezaei; Qhasem Sahraei; Mahboobeh Beiranvand (Gonabad University of Medical Sciences, 2023)
Background: Infertility is a global problem that leads to psychological complications. Studies show that the psychological damage caused by infertility is far greater in women compared to men. Infertility reduces psychological well-being and causes infertility stress in infertile women. This study aims to determine the effectiveness of positive-thinking-based poetry therapy on infertility stress and psychological well-being in infertile women. Methods: This quasi-experimental research was conducted with a pre-test, post-test design and a control group. The statistical population included all infertile women. The sample size consisted of 46 women who were selected via the convenience sampling method. They were randomly assigned to experimental (n=23) and control groups (n=23). The experimental group received the package of positive-thinking-based poetry therapy which was compiled by the researchers, for eight 90-min sessions. The data was collected using the infertility stress questionnaire and the psychological well-being scale. The data were analyzed using multivariate and univariate analysis of covariance via the SPSS software, version 22. Results: The multivariate and univariate analysis of covariance results showed that positive-thinking-based poetry therapy has a positive and significant effect on improving infertility stress psychological and well-being in infertile women (P<0.05). Conclusion: According to the results, the change in mental attitude and emergence of positive emotions caused by the intervention of positive-thinking-based poetry therapy improved the infertility stress and psychological well-being of infertile women.